Gelak-Tawa sebagai Sinyal Transendensi Manusia - Heatubun, Fabianus Sebastian (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2014)
Comic dimension, on the one hand, is a human condition. It is a basic precondition for a human being called to be humanum, to be authentic, complete and true human being. ‘Comic’ (laughter) can be seen as a cultural product that has become nurtural. On the other hand, essentially comic or laughter is innate by origin. The nature of human can be conceived as a mammal that is able of distinguishing itself from other mammals. Thus human as mangel wesen (incomplete and weak being) by laughter has a capacity to transcend herself or himself, her or his body and whole life. It might even further to be said that that comic dimension has a capability to save humankind. In a mystical sense, when we laugh, we live through our most fundamental life. Laughter makes life more alive. Laughter becomes a sacred moment, for it is a blending event of the human with the divine, and in turn it brings back men and women to their original nature as a human being.